Dental anxiety and dental care - a comparison between Albania and Germany - Nertsa Cunoti; Rezart Qorri; Lisa Irmscher; Erda Qorri; Laura Magerfleisch; Hendrik Berth (BMC, 2024)
Abstract Background The present study is the first in Albania on dental fear and dental anxiety and also in the field of psychosocial medicine. The purpose of this study was to find out whether there are differences in dental anxiety using the Dental Anxiety Scale, their level of psychological distress using the Brief Symptom Inventory-18 and the evaluation of oral health among Albanian and German patients. Methods This study was conducted in the period from December 2019 to July 2020, a sample of N = 263 patients (133 Germans, 130 Albanians) using the Dental Anxiety Scale questionnaires to determine anxiety before dental treatment and the Brief Symptom Inventory-18 to evaluate psychological distress. Moreover, the patients answered questions regarding their oral health and dental care. In Germany, there were four refusals to entrance in the study due to various reasons, in contrast to Albania, where there were no refusals at all For the purposes of this study, data on both populations aged 14 years and older were used. Results The questionnaires results were calculated for all participants. The current subjective health status of Albanian patients was assessed to be significantly worse than that of German patients (p < 0,000). Germans were more susceptible to signs of Anxiety (p < 0,000), Depression and Somatization and scored higher on the Dental Anxiety Scale and the Global Severity Index (p < 0,000) than Albanian patients. Additionally Albanian patients scored significantly lower on the preventive care index (p < 0,000). Despite an elevated DAS anxiety level, German patients reported going to the dentist more frequently than Albanian patients. Conclusion The results showed that between both populations differences in dental anxiety, psychological distress and oral health exists. Patients from Germany report more psychological distress and described more dental anxiety compared to Albanian patients. Albanian patients reported not utilization on oral health care.The implementation of educational programs and preventive measures, would contribute to raising awareness about the importance of oral health and increased use of dental services.